(untitled) (Research, Society and Development, 2020)
Herbal practices often use plants with therapeutic potential for the treatment of pathologies, both in the “in natura” form, as well as in the medicinal form in health care. Brazil is generally characterized by great biodiversity, with a rich history of using medicinal plants to treat the health problems of the population from tribal groups. For this reason, it is of fundamental importance to make the population aware of the proper use of medicinal plants, since if used improperly they can produce potentially toxic substances. Therefore, the present study aimed to explain the experience on the dissemination of the rational use of herbal medicines by students of the Biological Sciences and Dentistry courses at the Federal University of Campina Grande (UFCG), contributing to the knowledge about the pharmacological properties of medicinal plants, ways of preparing teas and their indications. The knowledge was explained to the community, through technological resources (slides), to aid in the propagation of information. All stages of the herbal medicine production workshop were developed by students with the help of individuals present in the community. Guidance was given on homemade medicinal preparations and distribution of materials on the therapeutic use of some medicinal plants typical of the Northeast region. Thus, the experience had its contribution in bringing knowledge to the community about some therapeutic plants, contributing to the natural actions and health of the population.